Legal review on unfair force majeure clause in outbound package travel - Norhasliza, Ghapa; Farhanin, Abdullah Asuhaimi (2020)
The pandemic of covid-19 has an immense and rapidly changing impact on the everyday lives of the vast majority of citizens and companies. Businesses have been forced to close by legislation in particular. Even if the companies are still active, they frequently fail to meet their contractual responsibilities in the manner originally planned. Businesses that offer facilities for fun, relaxation, enjoyment and entertainment face unparalleled delays and cancellation. This includes the outbound travel package service. Force majeure is a common feature used by travel agencies in an outbound package travel